1993
DOI: 10.1007/bf00013997
|View full text |Cite
|
Sign up to set email alerts
|

Population dynamics of Melanoides tuberculata (Thiaridae) snails in a desert spring, United Arab Emirates and infection with larval trematodes

Abstract: A dense population of Melanoides tuberculata was found at a brackish (5.93-6.98x) desert spring in the United Arab Emirates. A total of 232-300 snails were measured and examined for larval trematodes during the period

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
7
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 6 publications
2
7
0
Order By: Relevance
“…The width of the thermal niche of M. tuberculata was similar to that of other freshwater animals including fishes and crayfish (Magnuson et al, 1979;Kivivuori, 1994). Our values are somewhat lower than the water temperatures from 20 to 31 1C typically inhabited by native and non-native populations of this species around the world (Ismail and Arif, 1993;Duggan, 2002;Rader et al, 2003). Similar temperature preferences have been documented for other freshwater gastropods.…”
Section: Temperature Selectionsupporting
confidence: 76%
“…The width of the thermal niche of M. tuberculata was similar to that of other freshwater animals including fishes and crayfish (Magnuson et al, 1979;Kivivuori, 1994). Our values are somewhat lower than the water temperatures from 20 to 31 1C typically inhabited by native and non-native populations of this species around the world (Ismail and Arif, 1993;Duggan, 2002;Rader et al, 2003). Similar temperature preferences have been documented for other freshwater gastropods.…”
Section: Temperature Selectionsupporting
confidence: 76%
“…Livshits and Fishelson (1983) reported that M. tuberculata snails are mainly algivorous or detrivorous. In relatively warm water at a desert spring in United Arab Emirates (29.0-31.0 o C) M. tuberculata snails reached 26.0 mm in length (Ismail & Arif 1993). Pointier (1993) reported that M. tuberculata snails from the marshy forest zone of Guadeloupe, French West Indies, reached a length of 10 mm after 4.5 months, 15 mm after 14 months, and in more than 30 months they reached 20 mm.…”
Section: Discussionmentioning
confidence: 99%
“…1988;Ismail 1990;Ismail & Arif 1991). This feature has attracted the attention to study its population dynamics, and reproduction (Livshits & Fishelson 1983;Dudgeon 1986;Ismail & Arif 1993).…”
Section: Introductionmentioning
confidence: 99%
“…Scale bar is 10 mm. of the red-rim melania in Morocco (Laamrani et al 1997), New Zealand (Duggan 2002), United Arab Emirates (Ismail and Arif 1993), and USA (Mitchell et al 2000;Fleming 2002) inhabited springs with temperatures between 21ЊC and 31ЊC.…”
mentioning
confidence: 99%